Aktivitas Fisik dan Hubungannya dengan Kejadian Diabetes Mellitus - Purnama, Agus; Sari, Nonita (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Diabetes mellitus is a serious problem and became one of the leading causes of death in Indonesia. In addition, many studies suggest that prevalence will continue to increase in 2030. The high prevalence needs to be prevented from now on. One way to prevent the addition of the incidence of diabetes is to know the relationship of physical activity of any person to experience diabetes. The purpose of this study was to determine the relationship of physical activity to the incidence of diabetes mellitus. This research method uses analytic descriptive design with cross sectional approach. The population in this study were 30 respondents. Sampling technique using Total population and obtained sample 30 respondents. The data is processed and performed calculation using a computerized data program. This research use Chi square test with result of research indicate that there is relation of physical activity to incidence of diabetes mellitus (P value = 0.009 with OR = 11,000). Suggestions in this study is expected health workers are able to provide counseling and counseling to families and patients with DM in order to have awareness to always do regular physical activity, make lifestyle changes to a better direction.